The social function of Programa Saúde na Escola: formation for new capital sociability? - Aline Fabiane Barbieri; Amélia Kimiko Noma (Universidade Federal de Santa Catarina, 2017)
This paper analyzes the social function of the School Health Program (PSE) based on a bibliographical and documentary study, which used a historical materialist methodology. It finds that this program is articulated to three components of the "Third Way" neoliberal educational project:  the notion of "active civil society" and the "third sector" project; the ideology of "social capital" and the theory of "human capital". The study found that the social function of the School Health Program is to collaborate in the spread of conservative ideological reasoning, which is compatible with the construction of a new standard of sociability in Brazil, through formation of active subjectivities in healthcare. The program also serves to mitigate expressions of the "social question" and maintain a workforce that can meet the needs of capitalist exploitation.